2023
DOI: 10.3390/nano13060974
|View full text |Cite
|
Sign up to set email alerts
|

Nanobionics: A Sustainable Agricultural Approach towards Understanding Plant Response to Heavy Metals, Drought, and Salt Stress

Abstract: In the current scenario, the rising concentration of heavy metals (HMs) due to anthropogenic activities is a severe problem. Plants are very much affected by HM pollution as well as other abiotic stress such as salinity and drought. It is very important to fulfil the nutritional demands of an ever-growing population in these adverse environmental conditions and/or stresses. Remediation of HM in contaminated soil is executed through physical and chemical processes which are costly, time-consuming, and non-susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 86 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…Unfortunately, the authors did not provide information on the production cost of the conventional Fe used, which makes it challenging to conduct a comparative cost-benefit analysis. A previous review 216 found that eggplant yield increases were 24% and 52% for conventional and nano-CuO fertilizers, respectively. A 25 g bottle of conventional CuO cost 18.50 $, while nano-CuO costs 44.00 $, resulting in a gain of 4637.00 $ per acre with an investment of 26.00 $ (44.00 $-18.50 $).…”
Section: Nanofertilizers Economics Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…Unfortunately, the authors did not provide information on the production cost of the conventional Fe used, which makes it challenging to conduct a comparative cost-benefit analysis. A previous review 216 found that eggplant yield increases were 24% and 52% for conventional and nano-CuO fertilizers, respectively. A 25 g bottle of conventional CuO cost 18.50 $, while nano-CuO costs 44.00 $, resulting in a gain of 4637.00 $ per acre with an investment of 26.00 $ (44.00 $-18.50 $).…”
Section: Nanofertilizers Economics Analysismentioning
confidence: 98%
“…215 Cellular organelles produce reactive oxygen species (ROS) in stress situations, which are the main symptom of abiotic stress. 216 Plants possess enzymatic mechanisms to cope with the oxidative stress they are subjected to by the environment. 201 On the other hand, plants suffer the effects of such a situation when the defense system fails.…”
Section: Nano-fertilizers Mitigate Abiotic Stressesmentioning
confidence: 99%
“…Their synthesis is mediated by the enzyme phytochelatins synthase (PCs), which is activated in response to metal exposure. This activation leads to the chelation of toxic metal ions, such as Cd, Cu, and Zn, thus mitigating their toxicity to plants [127][128][129].…”
Section: Role Of Metallothioneins and Pcsmentioning
confidence: 99%
“…The reaction involves the gamma-glutamylcysteine moiety of glutathione being polymerized to form PCs, which can bind to and detoxify metals/metalloids within the plant cells. This process not only plays a significant role in the detoxification and tolerance of metal/metalloids but also highlights the potential for phytoremediation applications, where plants are used to remove pollutants from the environment [127,129].…”
Section: Role Of Metallothioneins and Pcsmentioning
confidence: 99%
See 1 more Smart Citation